A novel "humanized mouse" model for autoimmune hepatitis and the association of gut microbiota with liver inflammation. Issue 5 (25th August 2015) - Yuksel, Muhammed; Wang, Yipeng; Tai, Ningwen; Peng, Jian; Guo, Junhua; Beland, Kathie; Lapierre, Pascal; David, Chella; Alvarez, Fernando; Colle, Isabelle; Yan, Huiping; Mieli‐Vergani, Giorgina; et al.
<x xml:space="preserve">Abstract</x> Autoimmune hepatitis (AIH) in humans is a severe inflammatory liver disease characterized by interface hepatitis, the presence of circulating autoantibodies, and hyper‐gammaglobulinemia. There are two types of AIH, type 1 (AIH‐1) and type 2 (AIH‐2), characterized by distinct autoimmune serology. Patients with AIH‐1 are positive for anti–smooth muscle and/or antinuclear autoantibodies, whereas patients with AIH‐2 have anti–liver kidney microsomal type 1 and/or anti–liver cytosol type 1 autoantibodies. Cytochrome P4502D6 is the antigenic target of anti–liver kidney microsomal type 1, and formiminotransferase cyclodeaminase is the antigenic target of anti–liver cytosol type 1. It is known that AIH, both types 1 and 2, is strongly linked to the human leukocyte antigen (HLA) alleles ‐DR3, ‐DR4, and ‐DR7. However, direct evidence of the association of HLA with AIH is lacking. We developed a novel mouse model of AIH using the HLA‐DR3 transgenic mouse on the nonobese‐diabetic background by immunization of HLA‐DR3– and HLA‐DR3+ nonobese‐diabetic mice with a DNA plasmid, coding for human cytochrome P4502D6/formiminotransferase cyclodeaminase fusion protein. Immunization with cytochrome P4502D6/formiminotransferase cyclodeaminase leads to a sustained elevation of alanine aminotransferase, development of antinuclear autoantibodies and anti–liver kidney microsomal type 1/anti–liver cytosol type 1 autoantibodies, chronic immune cell infiltration, and parenchymal fibrosis on liver histology in HLA‐DR3+ mice. Immunized mice also showed an enhanced T helper 1 immune response and paucity of the frequency of regulatory T cells in the liver. Moreover, HLA‐DR3+ mice with exacerbated AIH showed reduced diversity and total load of gut bacteria. Conclusion: Our humanized animal model has provided a novel experimental tool to further elucidate the pathogenesis of AIH and to evaluate the efficacy and safety of immunoregulatory therapeutic interventions in vivo. (Hepatology 2015;62:1536–1550)